Evaluation the protective impact of Cape gooseberry (Physalis peruviana L.) extract against benzo(a)pyrene induced DNA damage and gene expression change in male rats - Lamiaa M. Salem (Journal of Global Pharma Technology, 2020)
Natural bioactive compounds have been increasingly investigated against carcinogenic agents to prevent tumour progression. Thus, several active ingredients exist in different herbs and medicinal plants exhibited preventive impact against benzo(a)pyrene (BaP) induced carcinogenesis. In the present study, the efficacy of Cape gooseberry fruit (CGF) extract was investigated against BaP induced genetic toxicity in Swiss albino male rats. Male rats (n=90) were allocated in several groups exposed to BaP and/or several doses of CGF extract (100, 150 and 200 mg/kg b.w.). Assessment of DNA damage, generation of DNA adducts and expression alteration of stress (Hsp70a, CYP450) and antioxidant (GST) related genes were conducted. The results showed that treatment of BaP-exposed rats with different doses of CGF extract was able to prevent the genetic toxicity in the forms of DNA damage and DNA adducts as well as gene expression alteration induced by BaP. The results suggested that CGF extract-BaP interaction may reflect the extract efficacy against genotoxicity induced by chemotherapeutic drugs that are metabolized by antioxidant enzymes.